A Feasibility study on embedding phase change materials in jackets in the Philippine market - Arrienda, Ma. Stephanie B.; Blancada, Victor Angelo B.; Claveria, Angelic D.; Fabico, Rachelle Joy S. (College of Engineering, 2013)
The study aims to assess the feasibility of PRESCLO jacket, a jacket embedded with Phase Change Materials (PCM) to be manufactured and distributed in the Philippines. PCMs can absorb heat without a corresponding change in temperature, resulting in fabrics that can withstand drastic temperature changes. This technology is used by NASA for spacesuits, but now the application extends to articles of clothing such as jackets, which when donned, regulate human body temperature. The first step is to define the product, its characteristic, specifications, and features. By focusing on the core competency of the product, the potential customers and market shares were determined. Several marketing and sales strategies were also planned to attract these potential customers, which turned out to be motorcycle riders, people who are consistently exposed to varying temperatures and will reap the benefits from the product the most. One of the main sales strategies includes sponsoring a bike convention, planned to encourage high-end bike riders all over the Philippines to purchase PRESCLO jackets. After identifying the target market and the market mix, position in the market is then determined and demand forecasts were computed. The projected demand became the basis of production requirements and production planning. Consequently, operating requirements and accompanying costs were established. This includes evaluation of technological alternatives; identification of appropriate sets of equipment, raw materials, and labor that meet product specification and customer demand; assessment of possible geographical locations of the manufacturing facility; and finally identification of key people to run the business. As a conclusion to the technical study, an initial project cost of PHP 62 million is identified. Subsequent to identifying the start up cost, it was planned how to gather the necessary funds. It was determined that PHP 30 million of funds will be needed; PHP 15 million will be from loans, PHP 5 million from investors, and PHP 10 million from the owner. Financial statements were then prepared to determine the feasibility of operating the business, financial ratios and analyses made from these financial statements showed that the business is indeed profitable and financially feasible. Moreover, the analysis of the study was furthered by looking into the social profitability of the project. Having benefits of worth PHP 2.7 billion and total associated costs of PHP 865 million, the project of embedding phase change materials has a benefit-cost ratio of 3.09. This ratio indicates that the project is socially profitable.